Some open questions related to the minimum wage in the Republic of Serbia - Antić, Aleksandar; Urdarević, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The minimum wage in the Republic of Serbia is determined on the basis of the minimum wage determined in accordance with the Labour Law, working hours and taxes and contributions paid from wages. The minimum wage should be the minimum amount of money, which should enable employees to meet basic living needs. Unfortunately, its amount in practice is often not enough to provide for the basic living needs of employees and their family members. The employer should pay the minimum wage when, due to business disruption, he is unable to pay a wage that would be higher than it, ie. it should be an extraordinary phenomenon in the world of labor and capital. However, the minimum wage is becoming the rule of payment for employees in many industries in the Republic of Serbia.            One of the question related to the miniimum wage is whether it can be considered in accordance with the Decisions of the Government and the Socio-Economic Council as the net amount paid for the employment of all persons per hour, regardless of the legal basis of their work. This statement is suported by the used legal definition of minimum labour cost. For example, working under a contract on temporary and periodical jobs is the same as any other kind of work, even though work is conducted outside of employment relationship. According to the Law on Contributions for Complulsory Social Insurance, work within the employment relationship and work on the basis of contracts on temporary and periodical jobs are viewed equally from the perspective of contributions paid on wages.            In the light of international labour standards, according to the Minimum Wage Fixing Convention No. 131 of the International Labour Organization, each member of the International Labour Organization which ratifies this Convention undertakes to establish a system of minimum wages which covers all groups of wage earners whose terms of employment are such that coverage would be appropriate. Since the Republic of Serbia has ratified this Convention, it directly applies to all groups of workers, including those hired on the basis of contracts for temporary and occasional work.            Regarding the civil service system, the Law on Salaries in State Bodies and Public Servicies stipulates that the coefficient on the basis of which the basic salary of employees in state bodies and public services is determined expresses the complexity of work, responsibility, working conditions and education. The coefficient also contains an allowance in the name of compensation for food during work and recourse for the use of annual leave.            The practical question arose as to whether employees who are paid the minimum wage in the general regime of labour relations are entitled to a suplement in the name of compensation for food during work and recourse for the use of annual leave, ie. whether the minimum wage in the Republic of Serbia should include these allowances.              The authors will analyze the issues raised in the previous parts of the text, but also other issues related to the minimum wage and present views for their solution.
Keywords: minimum wage, ILO Convention 131, temporary and periodical jobs, food allowance during work, recourse for the use of annual leave